Design field controller for level, flow, temperature and networking using YOKOGAWA DCS - Rashid, Muhammad Mahbubur; Bhuiyan, Moinul; Imaliana, Bt Muzni; Mas Ernani, Bt Mustafa; Ferdaus, Meftahul (IOP Publishing, 2013)
The application of field controller is an emerging area on most engineering field. The digital field controller has been widely used in the industry since ages ago. In this project, distributed field controller is designed to measure temperature, level and flow of the system used in Industrial Automation using YOKOGAWA DCS network. Here local controller integrated with Distributed Control System by using Yokogawa CENTUM CS 3000. The field controller was designed based on the field plant. Apart from that, a networking was done through Ethernet, which work in dual redundancy.